2021
DOI: 10.1002/iju5.12266
|View full text |Cite
|
Sign up to set email alerts
|

Venous reconstruction using a Y‐shaped saphenous vein in kidney transplantation: A report of three cases

Abstract: Introduction Transplantation, especially, of the right kidney may be difficult to properly choose the main drainage vein due to abundance of renal veins with the thin wall and the small diameter. Therefore, we report three cases, wherein anastomosis‐related complications may be avoided by using a reconstructed Y‐shaped major saphenous vein graft. Case presentation The first case was a case of congestion when anastomosed with a trifurcated renal vein which ligated branch. The second case was a case of donated k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This reconstruction had no complications in any cases. This procedure has not been reported in uterine transplantation but was recently mentioned in the context of kidney transplantation [ 17 ]. Although the anatomy of the canine uterus differs distinctly from the human anatomy, the results of this study supply information regarding the anatomy of the canine uterus and immunosuppression during the transplantation process.…”
Section: Discussionmentioning
confidence: 99%
“…This reconstruction had no complications in any cases. This procedure has not been reported in uterine transplantation but was recently mentioned in the context of kidney transplantation [ 17 ]. Although the anatomy of the canine uterus differs distinctly from the human anatomy, the results of this study supply information regarding the anatomy of the canine uterus and immunosuppression during the transplantation process.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the IJU Case Reports, Miyauchi et al reported three living-donor kidney transplant cases which the two donor right renal veins were reconstructed using a major Y-shaped saphenous vein. 1 In the case of living-donor renal transplantation, the donor left kidney is usually selected because the right kidney has shorter venous length than the left kidney. 2 If there are minor abnormalities in the donor right kidney, the normal donor left kidney is preserved.…”
Section: Editorial Commentmentioning
confidence: 99%
“…4 When there are two veins, as reported in Miyauchi et al's study, this Y-shaped saphenous vein graft seems to be effective in preventing outflow obstruction and to achieve the lengthening of the right allograft renal vein. 1 I would like to use the Y-shaped saphenous vein graft in case of short and multiple allograft renal veins. Tomokazu Shimizu M.D., Ph.D. 1,2,3 Departments of 1 Transplant Surgery and 2 Urology, Kidney Center, Toda Chuo General Hospital, Saitama, and 3 Department of Urology, Tokyo Women's Medical University, Tokyo, Japan houichi0114@yahoo.co.jp DOI: 10.1002/iju5.12285 This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.…”
Section: Editorial Commentmentioning
confidence: 99%